Salivary lipids – description and significance - Klichowska-Palonka, Małgorzata; Bachanek, Teresa (Journal of Stomatology, 2015)
Lipids in the human body play an important role in the physiological and pathological processes. Laboratory analysis of blood lipid parameters is an important test of health and disease. Saliva contains many organic compounds belonging to the group of proteins, carbohydrates and lipids. Studies provide important information about organic products of saliva, but the lipid fraction is the least described group. Among numerous studies on the human saliva profile few works relate to the lipid fraction, and the information are often incomplete. This review presents the literature from the first reports until the current state of knowledge on salivary lipids. It contains information about the types and concentrations of lipids in saliva in physiology and pathology, correlations with systemic diseases, and diagnostic importance of the lipid fraction of saliva. It presents the area of knowledge which is rarely discussed in the Polish literature.